Self-assessment of vocational preparation and plans regarding undertaking employment among bachelor degree physiotherapy students of university-level schools of different educational orientations - Gotlib, Joanna; Prokopowicz, Katarzyna; Płaszewski, Maciej; Nowotny-Czupryna, Olga; Majcher, Piotr; Kułak, Wojciech; Grzegorczyk, Joanna; Bauer, Aleksandra; Barczyk, Katarzyna; Cabak, Anna; Białoszewski, Dariusz; Sierdziński, Janusz (Polish Journal of Public Health, 2010)
Introduction. A major change resulting from the separation of Bachelor- and Master-level studies is that after the completion of the Bachelor-level programme the student obtains a diploma of higher vocational education, i.e. a Bachelor’s degree, and becomes certified to practice the chosen profession. Aim. The objective of this study was to analyse the self-assessment of vocational preparation and vocational plans among physiotherapy students during their Bachelor programme studies at university-level schools of different educational orientations and compare self-ratings expressed by students of medical universities (MS), universities of physical education (PE), and other university-level schools (OU) during the first and third year of their Bachelor’s programme. Material and methods. The study involved the total of 593 students of 10 Polish universities (4 MS, 2 PE and 4 OU). The study was carried out in March and April 2009 among third-year students. The participation was voluntary. The data collected were the responses to an 88-question anonymous questionnaire designed by the authors. Statistical analyses utilised the chi-squared test (χ2) and the Kruskall-Wallis test at p<0.05 (STATISTICA 8.0 licensed to WUM). Results. The participants were most confident about their physical therapy skills (4.01) and least satisfied with their skills in the use of special techniques in physiotherapy (2.72) (p=NS). The students rated their orthopaedic competence as highest (3.56) and rheumatology skills as lowest (3.28). The participants were most confident about their ability to communicate with the patient (4.18) and least satisfied with their skills in communication with other members of the medical team (2.94) (p=NS). Conclusions. Students were of high opinion of their knowledge and skills in the area of physiotherapy and its clinical applications that they had gained during their Bachelor-level studies but it is necessary to bear in mind that this was their subjective opinion. The students’ self-assessment differed in the area of general competences such as preparation for conducting research or physical fitness, which could have been influenced by the educational orientations of their university-level schools.